Consciência metatextual e produção de textos argumentativos: estudo com um grupo de alunos do 1º ano do Ensino Médio na cidade de São Paulo - Dias, Judivania Dantas de Andrade (2012)
The purpose of this research is to investigate the effect of practicing turned to the Met textual ability, giving some instructions related to structure, organization and linguistics convention into the textual argumentative writing production, pointed to the students of the first grade in high school. The work was developed with eighteen students on the 1st grade in high school between fourteen to sixteen years old in a private school in São Paulo city. Intervention procedures were used as a control to tests before and after. The purpose of the pre-test was to analyze the students knowledge about the argumentative text structure. The first after test intended to analyze whether it happened an improvement in the ability evolution in the argumentative textual production of the student. During the second after test, the purpose was to certify if the results of the first test were kept. Eight interventions were accomplished between the before and after tests with the goal to develop some abilities in the argumentative textual production. The results show us that an intervention directed to a met textual awareness develops an ability of an argumentative textual production. The data explains that the simple way of teaching the system of argumentation, creates the ability of reflex and analyze texts, giving benefits to the learning and production textual of this genre